Customer management in B2B markets in the context of digitalization - M. V. Orlova; V. V. Orlov (Вестник университета)
The article is devoted to the problem of improving customer management in B2B markets in the context of digitalization. By analyzing the literature on the issues under study, the authors identified the main factors contributing to the transition from managing key customers to managing all the company’s customers in order to identify prospective customers, their development and strengthening relationships. Customer management based on the initial segmentation of customers, and then interaction with them in accordance with their position lead to a significant improvement in productivity. The analysis of foreign studies, as well as the survey conducted within the framework of this study, made it possible to justify the need to use modern strategies for managing key clients and marketing managing. The article identifies and systematizes the factors contributing to the effective implementation of strategies for managing key clients and marketing in the practical activities of modern companies, and also a questionnaire has been developed. The analysis of the research, in turn, revealed promising areas in the management of all the company’s clients, such as the gradual introduction of digital marketing methods, the use of technological advances (artificial intelligence and cloud computing), the provision of more personalized experience, the creation of scalable strategies, the development and implementation of domestic digital platforms for managing all the company’s clients.